Effect of transition metal (TM) doping on structural and magnetic properties in hexagonal YMn0.917TM0.083O3 systems. Issue 12 (December 2018) - Chen, Dong; Wang, Yu-Jia; Zhu, Yin-Lian; Ma, Xiu-Liang
Abstract: Suitable TM doping at the Mn site is an important access to manipulate magnetic properties of hexagonal YMnO3, however, it has not yet been systematically explored how the strength of antiferromagnetic interactions and the magnetic transition temperatures ( T N ) are modified in the doping YMn0.917 TM0.083 O3 systems. In the work, we have performed first-principles calculations to study the effect of TM doping on the structural and magnetic properties of hexagonal YMn0.917 TM0.083 O3 bulks; the results are combined with the available experimental results. The calculated results reveal that the planar TM-O bonds and O-TM-O angles of TMO5 bipyramid are both prominent structural features for the transformations of magnetic properties. We have also predicted the Ti, V, Cr and Fe doping effects on magnetic properties and further analyzed the TM electronic structures of TMO5 bipyramid in the YMn0.917 TM0.083 O3 (001)/MgO(001) film configurations, which could provide more understanding towards the designing of new generation multifunctional devices.